2017
DOI: 10.1103/physreve.96.013110
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the rotational friction coefficient of fractal aerosol particles in the transition regime using extended Kirkwood-Riseman theory

Abstract: We apply our extended Kirkwood-Riseman theory to compute the translation, rotation, and coupling friction tensors and the scalar rotational friction coefficient for an aerosol fractal aggregate in the transition flow regime. The method can be used for particles consisting of spheres in contact. Our approach considers only the linear velocity of the primary spheres in a rotating aggregate and ignores rotational and coupling interactions between spheres. We show that this simplified approach is within approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Furthermore, it only works for spheres and it can therefore be challenging to differentiate a single sphere from a cluster. Indeed, in the case of two particles joined together such as a nanodumbbell, the expected linewidth should be smaller by 8 % compared to a sphere (independently from the size of the spheres and assuming a stochastic rotational motion of the dumbbell) [41], which is comparable to the statistical uncertainty of the measurement shown here. In comparison, a change in mass by a factor 2 for a spherical object corresponds to a reduction in linewidth by 21 %, easier to measure.…”
Section: Size Estimationmentioning
confidence: 53%
“…Furthermore, it only works for spheres and it can therefore be challenging to differentiate a single sphere from a cluster. Indeed, in the case of two particles joined together such as a nanodumbbell, the expected linewidth should be smaller by 8 % compared to a sphere (independently from the size of the spheres and assuming a stochastic rotational motion of the dumbbell) [41], which is comparable to the statistical uncertainty of the measurement shown here. In comparison, a change in mass by a factor 2 for a spherical object corresponds to a reduction in linewidth by 21 %, easier to measure.…”
Section: Size Estimationmentioning
confidence: 53%
“…Unfortunately, in many practical situations aerosol particles are fractal-like aggregates in the transition flow regime, so a different approach is needed to analyze their rotational behavior. Recently, we (Corson et al 2017c) demonstrated that our extended Kirkwood-Riseman (EKR) method (Corson et al 2017a,b) can be applied to the rotational problem.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…In addition, one would now need to invert a 6N-by-6N matrix (instead of a 3Nby-3N matrix, as in our current method) to obtain the translational, rotational, and coupling friction tensors. .See Corson et al [2017c] for further discussion./ Rotational and coupling hydrodynamic interactions are weaker (i.e., lower order in r ij ) than the translational hydrodynamic interactions described by T $ ij , so we ignore these effects in our EKR method. The resulting error is appreciable (around 30-40%) for very small, dense (i.e., high fractal dimension) aggregates but decreases as the aggregate size (and thus the average distance between spheres) increases (Corson et al 2017c).…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 2 more Smart Citations